Pembinaan Guru Inspiratif: Pelatihan Supervisi Akademik Berorientasi Coaching dalam Program Pendidikan Guru Penggerak di Lombok Timur - Ramlah H A. Gani; Nunung Supratmi; Titin Ernawati; Herman Wijaya (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2024)
The PGP program is an important initiative in improving the quality of education in East Lombok. However, to ensure the success of this program, an effective academic supervision approach is needed, especially one that is oriented towards a coaching mindset. The PKM aims to provide coaching-oriented academic supervision training to teacher leaders in East Lombok. By doing so, it is expected that the teachers will be able to improve their skills in leading and managing the learning process effectively. Training methods include workshop sessions, interactive discussions, case studies, and practical simulations. The training was conducted face-to-face using the coaching mindset as the main foundation. The results of the training showed significant improvement in the understanding and skills of the lead teachers in implementing academic supervision using the coaching approach. The participants were able to identify strengths and areas of development in the learning process, and were able to provide constructive and growth-oriented feedback. In conclusion, coaching-oriented academic supervision training in the PGP program in East Lombok is an important step towards improving the competence of teacher leaders and in turn, the quality of education in the area.